1980
DOI: 10.3109/03008208009152356
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructural Characteristics of Abnormal Collagen Fibrils in Various Organs

Abstract: Quite unrelated diseases affecting different organs can lead to the appearance of abnormal collagen fibrils, which may be due to genetic disorders, transformation of mesenchyme cells, increased collagen synthesis or a change in the ground-substance. The simultaneous appearance of abnormal collagen fibrils and matrix vesicles containing lysosomal enzymes in the majority of our electron photomicrographs suggests an alteration in the ground-substance as a main cause of non-hereditary collagen dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The combined existence of thicker and thinner fibrils has been reported in some forms of skeletal dysplasias such as osteogenesis im perfecta type IV [13], Therefore the term 'collagen dysplasia', according to Staubesand and Fischer [12] may be used for the idio pathic form of CTS. The irregularity of the collagen fibrils in their cross-sectional out lines, as described by Staubesand and Fischer [ 12], may be interpreted as a prior form of 'collagen dysplasia', whereas we observed the subsequent stage where collagen fibrils have already been separated completely. The exis tence of varying diameters of collagen fibrils in idiopathic CTS leads to the following questions: To which type of collagen do these fibrils belong and where and why do these thick fibrils originate [4]?…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The combined existence of thicker and thinner fibrils has been reported in some forms of skeletal dysplasias such as osteogenesis im perfecta type IV [13], Therefore the term 'collagen dysplasia', according to Staubesand and Fischer [12] may be used for the idio pathic form of CTS. The irregularity of the collagen fibrils in their cross-sectional out lines, as described by Staubesand and Fischer [ 12], may be interpreted as a prior form of 'collagen dysplasia', whereas we observed the subsequent stage where collagen fibrils have already been separated completely. The exis tence of varying diameters of collagen fibrils in idiopathic CTS leads to the following questions: To which type of collagen do these fibrils belong and where and why do these thick fibrils originate [4]?…”
Section: Discussionsupporting
confidence: 66%
“…So far only little attention has been directed to wards the morphology of the transverse car pal ligament in the idiopathic CTS [1]. Pa tiala et al [7] reported varying light mi croscopical aspects of the transverse carpal ligaments of surgical biopsies, ranging from In an ultrastructural inves tigation Staubesand and Fischer [12] re ported the existence of abnormal collagen fibrils in the transverse carpal ligaments of 9 patients with CTS. These abnormal collagen fibrils, particularly thick ones, showed var ious degrees of irregularity in their cross-sec tional outline, ranging from slight peripheral fraying up to an indented circumference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1989;Jones et al. 1994] and fibrillation and dystrophic collagen associ ated with atherosclerosis, experimental saccular aneurysms and arteriovenous shunts [Staubesand and Fischer. 1980;Slehbens and Martin.…”
Section: Hemodynamically Induced Intimal Proliferationmentioning
confidence: 99%
“…First, it is not merely the quantity of collagen that affects myocardial stiffness but the arrangement of the collagen bundles, which cannot be assessed using this technique. Secondly, it has been shown that the collagen content of the vessel wall and of the perivascular spaces may be markedly increased in experimental hypertension (Staubesand & Fischer, 1980). This connective tissue contributes significantly to the overall collagen content but confers little to mechanical stiffness of the heart and cannot be distinguished from the interstitial collagen by a hydroxyproline assay (Thiedemann et al 1983).…”
Section: mentioning
confidence: 99%